Standardization of Pricking Stage of Chir Pine and Khair Germinants in Root Trainers - Gera, Mohit; Koul, Ajay Raj; Gera, Neelu (Indian Forester, 2002)
A trial was carried out to standardize the best stage for transplanting the germinants of Pinus roxburgii (Chir pine) and Acacia catechu (Khair) in the root trainers to obtain maximum survival. Transplanting of germinants of Chir pine in 11-13 days and of Khair in 10-12 days after sowing, gave maximum survival percent. Poor survival of transplanted germinants was recorded in case of direct sowing in both the species and transplantation at first leaf (needle) stage in case of Chir pine.